2021
DOI: 10.1155/2021/5164100
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism, Clinical Significance, and Treatment Strategy of Warburg Effect in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a primary malignancy of the liver and the third leading cause of cancer death worldwide. The incidence of HCC accounts for more than 90% of primary HCC. Like most solid malignancies, the occurrence and development of HCC are closely related to the Warburg effect. The Warburg effect of HCC is mainly manifested as increased glucose uptake by HCC cells, increased glycolysis, restricted mitochondrial oxidative phosphorylation, increased pentose phosphate pathway in HCC cells, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…As mentioned earlier, proteome and metabolome changes are the downstream consequence of cell signaling, and the tumor tissue may already be in a low-glucose equilibrium if insufficient materials are supplied. Additionally, the traditional Warburg effect has been increasingly challenged due to different cancer types and diverse tumor microenvironments, and these phenomena might also be caused by tumor stromal cells, resulting in the observation of a reverse Warburg effect [51][52][53]. Moreover, glutamate was significantly increased in advanced-stage HCC, indicating the activation of an alternative energy generation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, proteome and metabolome changes are the downstream consequence of cell signaling, and the tumor tissue may already be in a low-glucose equilibrium if insufficient materials are supplied. Additionally, the traditional Warburg effect has been increasingly challenged due to different cancer types and diverse tumor microenvironments, and these phenomena might also be caused by tumor stromal cells, resulting in the observation of a reverse Warburg effect [51][52][53]. Moreover, glutamate was significantly increased in advanced-stage HCC, indicating the activation of an alternative energy generation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Copper depletion in mitochondria switches cellular metabolism from cellular respiration to glycolysis (50). The Warburg effect in HCC is mainly characterized by increased glucose uptake, elevated glycolysis, restricted mitochondrial OXPHOS, heightened glutamine catabolism, and enhanced pentose phosphate pathway in HCC cells, and is closely associated with HCC cell proliferation, migration, invasion, apoptosis, immune escape, chemotherapy suppression and treatment failure (51). Thus, the role of copper in hepatocarcinogenesis indicated that cuproptosis may be intimately associated with alleviation of mitochondrial dysfunction and reduction of glycolysis in HCC patients, providing an idea into the discovery of novel therapies related to cuproptosis for liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[97] BAY-876 is a Glut1 antagonist, and single injection of microcrystalline BAY-876 into HCC tumor tissues led to inhibition of glucose uptake, proliferation, and epithelial-to-mesenchymal transition of HCC in mice. [191] Liu et al [152] reported that aspirin reduced glucose uptake and hepatoma proliferation in vitro and in mice by downregulating Glut1. Everolimus is a mTOR inhibitor, and it suppresses glucose uptake and tumor angiogenesis by reducing HIF-1α expression (Table 1).…”
Section: Targets In the Warburg Effectmentioning
confidence: 99%
“…For example, downregulating Glut1 expression by long non-coding RNA (lncRNA) SLC2A1-AS1 suppressed the proliferation and metastasis of HCC, 190 and targeting Glut1 by siRNA suppressed CCA cell migration and invasion 97 . BAY-876 is a Glut1 antagonist, and single injection of microcrystalline BAY-876 into HCC tumor tissues led to inhibition of glucose uptake, proliferation, and epithelial-to-mesenchymal transition of HCC in mice 191 . Liu et al 152 reported that aspirin reduced glucose uptake and hepatoma proliferation in vitro and in mice by downregulating Glut1.…”
Section: Introductionmentioning
confidence: 99%